(untitled) (Zaranie Śląskie, 2025)
On 30 September 2016, in accordance with the permission of the Lower Silesian Conservator of Monuments in Wrocław (branch office in Wałbrzych) and in cooperation with the parish priest of the local parish, Canon Józef Siemasz, an interdisciplinary research team undertook the exploration of one of the nine sarcophagi placed in the crypt of St. Nicholas Church in Świebodzice. The work was coordinated by the Upper Silesian Branch of the Polish Archaeologists’ Scientific Association. The team consisted of specialists with many years of experience, who had previously researched, among others, the Promnitz crypt in the Church of All Saints in Pszczyna, and who represented various scientific disciplines: Prof. Henryk Głąb (anthropologist, Jagiellonian University, Department of Anthropology), Prof. Małgorzata Grupa (archaeologist, conservator of monuments, specialist in historic fabrics, Nicolaus Copernicus University in Toruń, Institute of Archaeology and Ethnology), Dr Mirosław Furmanek (archaeologist, University of Wrocław, Institute of Archaeology), Sławomir Kulpa (archaeologist, Museum in Wodzisław Śląski), Dr Arkadiusz Kuzio-Podrucki (historian, Silesian Culture Centre in Nakło Śląskie, currently employed at the Institute of Regional Research of the Silesian Library in Katowice), Agata Sady (archaeobotanist, Silesian Museum in Katowice). The conservation work was supervised by Agnieszka and Tomasz Trzos (art conservators, A.P. Monument Conservation Workshop in Tychy). The crypt in the church in Świebodzice, which is a unique and relatively well-preserved structure, was established in the basement of the southern chapel adjacent to the presbytery, where deceased members of the Hochberg family, including the owners of nearby Książ, were laid to rest. Above the entrance to the chapel there is a cartouche with the Hochberg coat of arms. Preliminary findings show that the structure was actively used for over 200 years between 1662 and 1868.